SEJARAH BERDIRINYA MASJID AGUNG AT-TAQWA SEBAGAI OBJEK WISATA RELIGI DI KUTACANE - Syahrul Nizar Saragih; Elisa Sunarti Manurung; Amelia Br Karo; Duana Angel Simanjuntak; Cinthia Margaretha Simamora (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Great Mosque of At-Taqwa Kutacane is a historic mosque closely associated with the establishment of Aceh Tenggara Regency. The mosque was initiated by Lettu Syahadat in 1956 and was constructed between 1961 and 1962 as part of efforts to support the religious life of the community. Throughout its development, the mosque underwent three renovations before being rebuilt in 2009 and completed in 2016. Since then, the Great Mosque of At-Taqwa Kutacane has served not only as a place of worship but also as a center for various religious activities and one of the religious tourism destinations in Aceh Tenggara. The mosque has contributed to religious life by encouraging worship activities, to the local economy through trading activities around the mosque, and to cultural preservation through the use of traditional Alas and Gayo ornaments that characterize the mosque’s architecture.